Speed limits and vehicle accidents in built-up areas: The impact of 30 km/h zones - Davide Cerruti; Massimo Filippini (ETH Zurich, CER-ETH - Center of Economic Research, 2021)
Vehicle accidents represent an important source of externalities from driving. Using a detailed dataset on accident location and characteristics in Switzerland, we estimate the effect of switching from a 50 km/h speed limit to a 30 km/h limit on the probability of vehicle accident injuries. After an initial country-wide analysis, we exploit the quasi-experimental variation of the timing of introduction of 30 km/h zones in the municipality of Basel, using a difference in differences strategy. We find a significant reduction in accident severity due to lower speed limits, and substantial heterogeneities based on the circumstances of the accident.
Keywords: R41; R42; R48; H41; 330; Speed limits; vehicle accidents; 30 km/h zones; externalities; road transport; urban roads